2010
DOI: 10.5194/angeo-28-417-2010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting amplitude of solar cycle 24 based on a new precursor method

Abstract: Abstract. It is shown that the monthly smoothed sunspot number (SSN) or its rate of decrease during the final years of a solar cycle is correlated with the amplitude of the succeeding cycle. Based on this relationship, the amplitude of solar cycle 24 is predicted to be 84.5±23.9, assuming that the monthly smoothed SSN reached its minimum in December 2008. It is further shown that the monthly SSN in the three-year period from 2006 through 2008 is well correlated with the monthly average of the intensity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
(35 reference statements)
3
14
0
1
Order By: Relevance
“…[15] Although the actual maximum sunspot number will be determined in a few years, we need to select the maximum sunspot number for solar cycle 24 from some predicted values to apply this statistical model. The maximum sunspot number of the solar cycle 24 was predicted to be as low as 75 by Svalgaard et al [2005], while based on a precursor method, it was predicted to be 84 [Yoshida and Yamagishi, 2010]. Although many other predictions are reviewed by Pesnell [2012], it is noteworthy that the prediction method by Yoshida and Yamagishi [2010] is one of the simplest, and it is consistent with many important observations of the weak polar field [Svalgaard et al, 2005] as well as the cycle length [Hathaway et al, 2002;Watari, 2008].…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…[15] Although the actual maximum sunspot number will be determined in a few years, we need to select the maximum sunspot number for solar cycle 24 from some predicted values to apply this statistical model. The maximum sunspot number of the solar cycle 24 was predicted to be as low as 75 by Svalgaard et al [2005], while based on a precursor method, it was predicted to be 84 [Yoshida and Yamagishi, 2010]. Although many other predictions are reviewed by Pesnell [2012], it is noteworthy that the prediction method by Yoshida and Yamagishi [2010] is one of the simplest, and it is consistent with many important observations of the weak polar field [Svalgaard et al, 2005] as well as the cycle length [Hathaway et al, 2002;Watari, 2008].…”
Section: Resultsmentioning
confidence: 70%
“…The maximum sunspot number of the solar cycle 24 was predicted to be as low as 75 by Svalgaard et al . [], while based on a precursor method, it was predicted to be 84 [ Yoshida and Yamagishi , ]. Although many other predictions are reviewed by Pesnell [], it is noteworthy that the prediction method by Yoshida and Yamagishi [] is one of the simplest, and it is consistent with many important observations of the weak polar field [ Svalgaard et al ., ] as well as the cycle length [ Hathaway et al ., ; Watari , ].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In our previous paper (Yoshida and Yamagishi, 2010), we showed that the SSNs at points 1, 2, 3, 4, and 5 years before the minimum or the minimum SSN are correlated with the maximum SSN of the succeeding cycle, and that the SSN at a point 3 years before the minimum exhibits the strongest correlation. Yoshida and Sayre (2012), then, showed that a better correlation is obtained when the average SSN over a cycle is taken instead of the maximum SSN, and that the correlation coefficient becomes the largest when the average SSN is calculated by dividing cycles at a point 3 years before the minimum.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown previously that the sunspot number (SSN) at a point 3 years before the minimum is well correlated with the maximum SSN of the succeeding cycle, and a better correlation is obtained when the maximum SSN is replaced by the average SSN over a cycle for which the average SSN is calculated by dividing cycles at a point 3 years before the minimum (Yoshida and Yamagishi, 2010;Yoshida and Sayre, 2012). Following these findings, we demonstrate in this paper that the correlation between the SSN 3 years before the minimum and the amplitude of the coming cycle differs significantly between even-numbered and oddnumbered cycles: the correlation is much better for evennumbered cycles.…”
mentioning
confidence: 99%